Faktor-Faktor Yang Mempengaruhi Tingkat Adopsi InovasiDan Kapabilitas Peternak Pada Kelompok Ternak Kambing - Anang Febri Prasetyo; Nurkolis Nurkolis; Ujang Suryadi (Jurnal Ilmiah Inovasi, 2017)
The development of livestock sub-sector is one of the strategic choices in supporting the national economy. Technological innovation plays a very big role in efforts to increase productivity and food production, especially livestock. Livestock groups are a good way to apply innovation to breeders. Institutional livestock is expected to be a means to increase technology adoption. This study aims to analyze the factors that affect the adoption of technology in dairy goat breeders. This research was conducted in Lembah Meru, Jember in August-September 2016, using descriptive method of case study. The results showed that internal factors such as age, educational level, farming experience, number of family members, livelihood, income level, motivation, and number of livestock ownership have no significant effect on technology adoption rate. Factors of age, education level, number of family members, and type of livelihood have a positive value on the rate of technology adoption. The capability of breeders in managing innovation shows high yields such as: (1) adaptability with innovation; (2) the ability to refine innovation; (3) the ability of commitment to innovation; (4) the ability to implement innovation; And (5) the ability to manage the available resources.